Poly(A)-specific ribonuclease regulates the processing of small-subunit rRNAs in human cells. Issue 6 (24th November 2016) - Ishikawa, Hideaki; Yoshikawa, Harunori; Izumikawa, Keiichi; Miura, Yutaka; Taoka, Masato; Nobe, Yuko; Yamauchi, Yoshio; Nakayama, Hiroshi; Simpson, Richard J; Isobe, Toshiaki; Takahashi, Nobuhiro
Abstract: Ribosome biogenesis occurs successively in the nucleolus, nucleoplasm, and cytoplasm. Maturation of the ribosomal small subunit is completed in the cytoplasm by incorporation of a particular class of ribosomal proteins and final cleavage of 18S-E pre-rRNA (18S-E). Here, we show that poly(A)-specific ribonuclease (PARN) participates in steps leading to 18S-E maturation in human cells. We found PARN as a novel component of the pre-40S particle pulled down with the pre-ribosome factor LTV1 or Bystin. Reverse pull-down analysis revealed that PARN is a constitutive component of the Bystin-associated pre-40S particle. Knockdown of PARN or exogenous expression of an enzyme-dead PARN mutant (D28A) accumulated 18S-E in both the cytoplasm and nucleus. Moreover, expression of D28A accumulated 18S-E in Bystin-associated pre-40S particles, suggesting that the enzymatic activity of PARN is necessary for the release of 18S-E from Bystin-associated pre-40S particles. Finally, RNase H–based fragmentation analysis and 3΄-sequence analysis of 18S-E species present in cells expressing wild-type PARN or D28A suggested that PARN degrades the extended regions encompassing nucleotides 5–44 at the 3΄ end of mature 18S rRNA. Our results reveal a novel role for PARN in ribosome biogenesis in human cells.